Isolation, identification, and pathogenicity of a NADC30-like porcine reproductive and respiratory disorder syndrome virus strain affecting sow production - Chang, Hao; Zheng, Jiaying; Qiu, Yingwu; Chen, Chuanxin; Li, Qunhui; Wu, Qianwen; Lin, Limiao; Zhao, Haishen; Zhou, Qingfeng; Gong, Lang; Sun, Yankuo; Zhang, Xiangbin; et al. (Frontiers in Veterinary Science, 2023)
Since it was first reported in 1987, porcine reproductive and respiratory syndrome virus (PRRSV) has caused several economic crises worldwide. The current prevalence of PRRSV NADC30-like stains causing clinical disease outbreaks in Chain is highly concerning. Immunization against and the prevention of this infection are burdensome for farming organizations as the pathogen frequently mutates and undergoes recombination. Herein, the genetic characterization of a NADC30-like strain (termed BL2019) isolated from a farm in Guangdong Province, China, was analyzed and its pathogenicity for piglets and sows was assessed. Results revealed that BL2019 exhibits a nucleotide homology of 93.7% with NADC30 PRRSV and its NSP2 coding region demonstrates the same 131aa deletion pattern as that of NADC30 and NADC30-like. Furthermore, we identified two recombination breakpoints located nt5804 of the NSP5-coding region and nt6478 of NSP2-coding region, the gene fragment between the two breakpoints showed higher homology to the TJ strain(a representative strain of highly pathogenic PRRSV) compared to the NADC30 strain. In addition, BL2019 infection in piglets caused fever lasting for 1 week, moderate respiratory clinical signs and obvious visual and microscopic lung lesions; infection in gestating sows affected their feed intake and increased body temperature, abortion rates, number of weak fetuses, and other undesirable 2 phenomena. Therefore, we report a NADC30-like PRRSV strain with partial recombination and a representative strain of HP-PRRSV, strain TJ, that can provide early warning and support for PRRS immune prevention and control.